The effect of the memory tape strategy on the achievement of expression material for primary school students - Hammadi, Hassan Khalbas (Al-Adab Journal, 2022)
This research aims to know the effect of the memory tape strategy on the expressive performance of the students of the five primary grades, and the research sample consisted of 93 male and female students distributed among the research groups (experimental and control). The statistic proved the effect of the memory tape strategy on expressive performance, and in this the researcher put forward a number of recommendations and proposals for his research.